The effects of bat photographs on emotions, attitudes, intentions, and wildlife value orientations. Issue 6 (2nd November 2021) - Straka, Tanja M.; Greving, Hannah; Voigt, Christian C.
ABSTRACT: Photo stimuli can be an effective way to engage people in wildlife conservation by stimulating emotions and cognitions. In a before-after experiment, we studied the effects of two sets of photo stimuli (bat under distress vs. bat with engaged human) on the observer's wildlife value orientations, emotions, attitudes (bats/conservation) and behavioral intentions to engage with wildlife conservation. After viewing the photos of distressed bats, participants felt significantly more anger, sadness, and compassion than participants who viewed the photos showing a bat with a human. Photos with distressed bats raised more positive attitudes toward wildlife conservation, higher intentions to engage in wildlife conservation, more mutualism values, and less domination values than photos showing bats with a human. Photographs of vulnerable and distressed bats might be an important tool to temporarily increase people's emotional reactions to bats, their wildlife value orientation and probably, more importantly, their support for bat conservation.